Different regimens of menopausal hormone therapy for improving sleep quality: a systematic review and meta-analysis. Issue 5 (31st May 2022) - Pan, Zhuo; Wen, Shu; Qiao, Xiaoyong; Yang, Meina; Shen, Xiaoyang; Xu, Liangzhi
Abstract: Importance: Long-term sleep disturbances in menopausal women are closely related to cardiovascular disorders, metabolic disorders, and cognitive impairment. At present, hormone therapy (HT) is a standard treatment for menopausal symptoms. However, it remains unclear whether HT can improve sleep quality. Objective: We did a systematic review and meta-analysis to assess the effects of different HT regimens on menopausal sleep quality. Evidence Review: We systematically searched MEDLINE, Embase, the Cochrane Central Register of Controlled Trials, PsycINFO, CINAHL, and Web of Science for randomized controlled trials of menopausal HT on sleep disturbances up to June 14, 2021. Information about ongoing and unpublished trials was collected by searching WHOICTRP and ClinicalTrials.gov. Our primary outcome was sleep quality with objective measurements. We estimated the standardized mean difference (SMD) using random-effects models. Findings: We identified a total of 3, 059 studies and finally included 15 studies in the meta-analysis. Compared with placebo, HT improved self-reported sleep outcomes (SMD = –0.13; 95% CI, –0.18 to -0.08, P   <  0.00001 and I 2  = 41%), but not sleep parameters measured by polysomnography. Subgroup analyses according to the regimen of HT showed that 17β-estradiol (17β-E2 ) (SMD = –0.34; 95% CI, –0.51 to -0.17, P   <  0.0001, and I 2  = 0%) and conjugated equine estrogens (SMD = –0.10; 95% CI, −0.12 to −0.07, P   <  0.00001, and I 2  = 0%) improved sleep quality. Moreover, transdermal administration (SMD = −0.35; 95% CI, −0.64 to −0.06, and P   =  0.02) was more beneficial than oral (SMD = −0.10; 95% CI, −0.14 to −0.07, and P   <  0.00001). In addition, the combination of estrogen and progesterone had a positive effect on sleep disturbance (SMD = −0.10; 95% CI, −0.13 to −0.07, P   <  0.00001, and I 2  = 0%), while estrogen monotherapy did not. The results showed that estrogen/micronized progesterone (SMD = −0.22; 95% CI, −0.37 to −0.06, P  = 0.007, and I 2  = 0%) and estrogen/medroxyprogesterone acetate (SMD = −0.10; 95% CI, −0.13 to −0.07, P   <  0.00001, and I 2  = 0%) could alleviate sleep disturbance. Conclusions and Relevance: HT has a beneficial effect on sleep disturbance to some extent, and the formulations and routes of administration of hormonal agents influence the effect size.